ANALISIS FAKTOR PENYEBAB MASYARAKAT LAMA MEMBANGUN RUMAH BERBENTUK PERSEGI PANJANG DAN KESESUAIANNYA TERHADAP PRINSIP RUMAH TAHAN GEMPA - Edriani, Annisa Fitria (Jurnal Ilmiah Teknik Sipil; Vol 27 No 1 (2023): Jurnal Ilmiah Teknik Sipil, Vol. 27 No. 1, Maret 2023DO - 10.24843/JITS.2023.v27.i01.p02, 2023)
As an earthquake prone area, building earthquake-resistant houses is a basic necessity for Bengkulu Province residents. The simple symmetrical house plan provides better structure to withstand earthquakes . Batu Kuning is a village located in Ulu Manna District, South Bengkulu Regency, Bengkulu Province. This village is a village that was affected by the earthquake in 2000 and 2007, as well as other earthquakes, although the impact was not as big as the two earthquakes. In the event of the earthquake, several houses were not heavily damaged or destroyed so they are still inhabited today. Observations made by the author found a tendency for the shape of the house to be simple, symmetrical and tend to be rectangular. The research method was carried out by distributing questionnaires to respondents with a total of 26 samples. The results of the questionnaire were processed and analyzed using the SPSS Version 26 program, which included data validity and reliability tests. The results obtained showed 26.72% in strength and resilience factors, 25.63% in economic and cost factors, 25.63% in construction factors, and 22.02% in customs and environmental factors. The dominant factor is the construction factor, with an indicator that the construction of a rectangular house is easier to work on. The suitability level of old people's houses with the principle of earthquake-resistant houses shows that 73.08% uses a continuous river stone foundation with a depth of more than 45 cm. 92.31% of the old community house structure in Batu Kuning Village, Ulu Manna Subdistrict, using wooden columns and beams. The use of lightweight (zinc) roofs is in accordance with the principles of building earthquake-resistant houses.